Economic Problems with Subsidies for Electric Vehicles. Issue 4 (30th September 2022) - Freebairn, John
Abstract : The use of motor vehicles in Australia generates external costs. The external costs are associated with government expenditure on road infrastructure, traffic congestion and road accidents as well as pollution. A subsidy for electric vehicles will reduce the pollution external cost, and more so as the share of electricity generated from fossil fuels declines. However, the subsidy‐induced increase in motor vehicle use will increase the other external costs. Also, the subsidy and the fall in excise tax revenue collected will add to the budget deficit. The phase‐in of electric vehicles provides an opportunity to reform special taxes and charges on the use of motor vehicles. The current ad hoc and long time ago imposed government taxes and charges on motor vehicles should be replaced with explicit taxes to internalise each of the external costs of motor vehicles.